The combination of BET and PARP inhibitors is synergistic in models of cholangiocarcinoma. (1st January 2020) - Fehling, Samuel C.; Miller, Aubrey L.; Garcia, Patrick L.; Vance, Rebecca B.; Yoon, Karina J.
Abstract: Our previous finding that the BET inhibitor (BETi) JQ1 increases levels of the DNA damage marker γH2AX suggested that JQ1 might enhance the sensitivity of tumor cells to PARP inhibitors (PARPi), which are selectively toxic to cells that harbor relatively high levels of DNA damage. To address this hypothesis, we evaluated the effect of a BETi (JQ1 or I-BET762) combined with a PARPi (olaparib or veliparib) in KKU-055 and KKU-100 cholangiocarcinoma (CCA) cell lines and of JQ1 with olaparib in a xenograft model of CCA. Each combination was more effective than any of the four drugs as single agents. Combination indices ranged from 0.1 to 0.8 at the ED50 for all combinations, indicating synergy and demonstrating that synergy was not limited to a specific combination. Mechanistically, downregulation of BETi molecular targets BRD2 or BRD4 by shRNA sensitized CCA cells to BETi as single agents as well as to the combination of a BETi + a PARPi. Our data indicate that combinations of a BETi with a PARPi merit further evaluation as a promising strategy for CCA. Highlights: BETi + PARPi exerts synergistic cytotoxicity in cholangiocarcinoma in vitro. JQ1 + olaparib inhibits growth of cholangiocarcinoma tumors in a preclinical model. shRNA-mediated decrease in BETi molecular targets increases the sensitivity of cholangiocarcinoma cells to BETi ± PARPi.